2002
DOI: 10.1002/etc.5620211030
|View full text |Cite
|
Sign up to set email alerts
|

Integrative assessment of benthic macroinvertebrate community impairment from metal‐contaminated waters in tributaries of the upper Powell River, Virginia, USA

Abstract: Benthic macroinvertebrate communities of the North Fork Powell River (NFP), southwest Virginia, USA, appear to be impacted by aluminum (Al) and iron (Fe) from acid mine drainage (AMD) beyond the zone of pH depression. As part of a watershed restoration project, we used integrative techniques, including water column, sediment, and in situ toxicity tests; sediment and water column chemistry; and habitat assessments, to detect AMD impacts. An analysis of variance, least significant difference post hoc test, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Macroinvertebrate abundance metrics have been shown to be highly variable and thus, lack sensitivity to ecosystem disturbance [41]. The low benthic macroinvertebrate density in shale-draining streams is consistent with those from related studies in which total abundances of macroinvertebrate communities are low in metal-contaminated streams [1,31,40]. Except for the Dipterans, densities of all other macroinvertebrate taxa were lower in shaledraining streams compared with those of the limestonedraining stream.…”
Section: Macroinvertebrate Metric Responsessupporting
confidence: 76%
See 1 more Smart Citation
“…Macroinvertebrate abundance metrics have been shown to be highly variable and thus, lack sensitivity to ecosystem disturbance [41]. The low benthic macroinvertebrate density in shale-draining streams is consistent with those from related studies in which total abundances of macroinvertebrate communities are low in metal-contaminated streams [1,31,40]. Except for the Dipterans, densities of all other macroinvertebrate taxa were lower in shaledraining streams compared with those of the limestonedraining stream.…”
Section: Macroinvertebrate Metric Responsessupporting
confidence: 76%
“…The most common observation of metal contamination from both laboratory and field studies is a reduced abundance and taxa richness of metalsensitive ephemeropterans [1,[29][30][31]. Low Ephemeroptera density and/ or taxa richness have been used widely as sensitive and reliable indicators of impacts of metals on benthic macroinvertebrate communities in aquatic ecosystems [8,9,31].…”
Section: Macroinvertebrate Metric Responsesmentioning
confidence: 99%
“…According to Sprague's (1985) (Table 2). Although neither federal nor state legislation establishes a maximum amount of aluminium allowed in the wastewater, Schmidt et al (2002) showed that dissolved aluminium concentrations as low as 0.18 mg Al .L -1 can strongly impair benthic macroinvertebrate communities. …”
Section: Chemical Variablesmentioning
confidence: 99%
“…The discharge of WTPs wastewater into waterways can introduce sediments in these environments and promote toxicity in aquatic organisms, mainly due to metals such as aluminium, high concentrations of solids, turbidity and increasing the biological oxygen demand (BOD). Untreated sludge released into an aquatic environment with low speed may cause sedimentation and thereby isolation of the benthic layer (Kress et al, 2004), colour changes, and disturbances in the chemical and biological composition on the receiving body (Barbosa et al, 2001;Schmidt et al, 2002).…”
Section: Macroinvertebrate Characterisationmentioning
confidence: 99%